دور عضو هيئة التدريس في دعم قيم المواطنة في الجامعات السعودية - الرويس، عزيزة سعد علي (جامعة كفر الشيخ - كلية التربية, 2018)
لقد أصبح العالم اليوم أشبه بقرية صغيرة في عصر العولمة، التي انعكست آثارها على السلوكيات وقيم المواطنة لدى الشباب. ولذلك هدف البحث الحالي إلى التعرف على دور أعضاء هيئة التدريس في الجامعات السعودية في دعم قيم المواطنة لدى الطلاب والطالبات، ومن ثم تقديم مقترحات لتفعيل هذا الدور الهام لأعضاء هيئة التدريس. ولتحقيق هذا الهدف، تحددت مشكلة البحث في السؤال الرئيس التالي: (ما دور أعضاء هيئة التدريس بالجامعات السعودية في دعم قيم المواطنة؟). وللإجابة على السؤال الرئيس للبحث، تم توظيف المنهج الوصفي التحليلي، وتطبيق استبانة على عينة عشوائية بلغ عددها (٣١٢) عضوا، تم اختيارهم عشوائيا بالطريقة الطبقية، من أعضاء هيئة التدريس المواطنين بكليات التربية بالجامعات الحكومية بمنطقة الرياض. وقد أظهرت النتائج أن مستوى دور أعضاء هيئة التدريس بالجامعات السعودية في دعم قيم المواطنة كان متوسطا. وحصل مجال الانتماء فقط على درجة عالية، أما مجالي المشاركة المجتمعية والواجبات فقد كانت الدرجة لمستوى أعضاء هيئة التدريس متوسطة، في حين أن درجة مجال الحقوق كانت منخفضة المستوى. وقد أوصت الباحثة بإعطاء التربية على المواطنة وتعزيز قيمها أولوية في الأنظمة التربوية؛ وأن يتم تضمينها في سياسات التعليم واستراتيجياته انطلاقا من الرؤية الوطنية، مع مطالبة الجامعات بالتركيز على دقة اختيار أعضاء هيئة التدريس بها، والتأكد من توفر معايير الأمن الفكري وقيم سلوكيات المواطنة المسؤولة لديهم، وتوفير البرامج التدريبية لتنمية مهاراتهم التدريسية في دعم قيم المواطنة لدى طلابهم.
Today, the world is witnessing rapid changes, due to the phenomenon of globalization with its multiple dimensions, which have had a significant impact on the behavior and values of citizenship among young people in particular. Therefore, the current research aimed to identify the role of faculty members in the universities in Saudi Arabia, to promote the values of citizenship, and then to present proposals to activate the primary role of the faculty members, to promote the values of citizenship. To achieve this goal, the research problem was identified in the following main question: (What is the role of the faculty members in supporting the Values of Citizenship in Saudi Universities?). To answer the main question, the research employed the analytical descriptive method and the application of a questionnaire to a stratified random sample of (312) members, have been selected from the citizen faculty members at the colleges of education in Riyadh Region. The results showed that the level of the role of faculty members in universities in promoting the values of citizenship was average. Field of belonging only obtained the high degree, the fields of community involvement and duties got average, while the degree of the field of rights was at low level. The researcher recommended that education of citizenship should be given priority in educational systems, and included in education policies and strategies based on the national vision. The universities should focus on the accuracy of the selection of faculty members who have the standards of intellectual security and citizenship values, and provide training programs to develop their teaching skills in support of the values of citizenship to their students.
Keywords: السياسة التعليمية -- التعليم الجامعي -- طلاب الجامعات -- أعضاء هيئة التدريس -- قيم المواطنة -- الجامعات السعودية -- مستخلصات الأبحاث